Indirect assessment of the maximum empirical activity (250 mCi) with respect to dosimetry concepts in radioiodine therapy of metastatic differentiated thyroid cancer. Issue 11 (November 2018) - Abuqbeitah, Mohammad; Demir, Mustafa; Kabasakal, Levent; Çavdar, İffet; Uslu-Beşli, Lebriz; Yeyin, Nami; Razavikhosroshahi, SayedBaresh; Sönmezoğlu, Kerim
Abstract : Aim: The development of reliable dosimetry models promotes the individualized therapy concept toward more success and less complications. This paper evaluates the traditional maximum empirical activity (250 mCi) and the benefit of joining two dosimetry approaches to optimize the therapeutic activity and radioiodine efficacy in metastatic differentiated thyroid cancer. Materials and methods: Nineteen (12 females and seven males) patients with metastatic differentiated thyroid cancer were included in the present study. The mean age of the patients was 46±16 years. The mean height and weight were 1.67±0.11 m and 76±18 kg, respectively. Radioiodine treatment was given by recombinant human thyrotropin stimulation in seven patients, and thyroxine withdrawal was successful for the rest 12 patients. The mean thyroid-stimulating hormone value was 68±34 μIU/ml, and the mean thyroglobulin value was 408±356 ng/ml before therapy. After radiotracer administration, lesion-absorbed dose was calculated in addition to red marrow dose estimation via two different models. Results: Total body and blood residence time was found to be 30±17 and 4.5±1.9 h, respectively. Red marrow absorbed dose was 0.535±0.262 Gy/100 mCi using the model accounts for red marrow dose surrogated by blood, and it was 0.398±0.212 Gy/100 mCi using a modified model with mean deviation of −24% (range: −19 to −31%). Red marrow absorbed dose was found to be 0.50±0.15 Gy/100 mCi in the levothyroxine withdrawal group, whereas it was 0.46±0.2 Gy/100 mCi for the patients who received recombinant human thyrotropin. Mean lesion-absorbed dose was 0.16±0.14 Gy/g/mCi. The speculated dose from 250 mCi iodine-131 was evaluated, as 65% of all lesions ( n =27) would receive at least 100 Gy, whereas the percentage of bone lesions that would receive at least 100 Gy was only 55%. Conclusion: Upon to this study, red marrow dose varies with type of preparation as that of medication withdrawal cases was slightly higher than exogenous thyroid-stimulating hormone. Involvement of lesion and red marrow dose assessment through dosimetry protocol seems indeed valuable to optimize safe and effective activity compared with the conventional regime with 250 mCi as maximum empirical activity.